Strategy for Deployment of Integrated Healthy Aging Regions Based Upon an Evidence-Based Regional Ecosystem—The Styria Model - Borrmann, Marcus; Lindner, Sonja; Hofer-Fischanger, Kathrin; Rehb, Robert; Pechstädt, Katrin; Wiedenhofer, Roswitha; Schwarze, Gabriele; Adamer-König, Eva-Maria; Mischak, Robert; Pfeiffer, Karl P.; Harer, Johann; Weinzerl, Katharina; et al. (Frontiers in Medicine, 2020)
In 2013, the European Commission founded the platform European Innovation Partnership on Active and Healthy Ageing. This platform builds on either individual commitment from partners or contribution from reference sites. The current publication aimed at developing an integrated region for active and healthy ageing based upon a co-creation process. A mixed model approach was used to establish an ecosystem on active and healthy ageing including stakeholders from macro-, meso- and microlevel in the province of Styria, Austria. Eight recommendations for the deployment of a healthy ageing region could be derived from the key results. The visibility and accessibility of healthy ageing products and services were evaluated as key factors for innovation in active and healthy ageing in the region. Health professionals were identified as key drivers for innovation towards active and healthy ageing in Styria. The project revealed capacities for healthy ageing in our region with the need to improve communication pathways between all levels of the public health system and market.